2009
DOI: 10.1016/j.pmrj.2008.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Abnormalities in the Shoulder and Wrist Joints of Asymptomatic Elite Athletes

Abstract: Asymptomatic elite athletes demonstrate MRI changes of the shoulder (swimmers and volleyball players) and wrist (gymnasts) similar to those associated with abnormalities for which medical treatment and sometimes surgery are advised. Given the somewhat high frequency of these asymptomatic findings, care must be taken to correlate clinical history and physical examination with MRI findings in these patients with symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 13 publications
1
37
1
3
Order By: Relevance
“…In one such study comparing MRI to arthroscopy reports, Ben-Galim et al found a false-positive rate of 47.2% for ACL tears in healthy subjects [100]. In another study, MRIs of wrists showed mild to moderate ligament injury in every case although all subjects (elite gymnasts) were asymptomatic [101].…”
Section: Mri -Not Always the Best Tools Of The Tradementioning
confidence: 99%
“…In one such study comparing MRI to arthroscopy reports, Ben-Galim et al found a false-positive rate of 47.2% for ACL tears in healthy subjects [100]. In another study, MRIs of wrists showed mild to moderate ligament injury in every case although all subjects (elite gymnasts) were asymptomatic [101].…”
Section: Mri -Not Always the Best Tools Of The Tradementioning
confidence: 99%
“…As a consequence, MRI risks inappropriate diagnoses and unnecessary treatments [9]. Wrist pain is common, and it is often difficult to identify discrete, objective pathophysiology that accounts for the symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Although asymptomatic structural changes have been reported in a variety of body regions, to our knowledge, no prior investigation has systematically evaluated the plantar heel region in asymptomatic runners, a group at risk for developing heel abnormalities. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Consequently, the primary purpose of this investigation was to determine the prevalence and spectrum of asymptomatic sonographically determined structural changes in the plantar fascia and plantar heel pad among experienced runners without a history of heel pain. On the basis of our preliminary observations, we hypothesized that more than 50% of asymptomatic runners would have at least 1 structural abnormality in 1 heel, as defined by the following: (1) presence of vascularization on power Doppler sonography, (2) nonuniform heterogeneous echo texture of the plantar heel pad, (3) abnormal plantar heel pad thickness (uncompressed heel pad thickness <12 or > 28 mm), 15,36 (4) abnormal plantar heel pad compressibility (heel pad compressibility index <0.45 or >0.75), 15 (5) abnormal plantar fascia thickness (>4 mm), 1 and (6) abnormal plantar fascia echo texture.…”
mentioning
confidence: 99%